Multitrait selection for higher agronomic and tuber yield-related traits in tiger nut (Cyperus esculentus L.) genotypes - Asare, P.A.; Adewumi, A.S.; Twumasi, P.; Afutu, E.; Adu, M.O. (2025)
The tiger nut is a valuable crop that has been overlooked and underutilized. The tubers of this plant are highly valued for their nutritional benefits and health advantages. This study aimed to evaluate the genetic potential of 42 tiger nut genotypes using a multitrait index based on factor analysis and genotype‐ideotype distance (MGIDI). The experiment involved a randomized complete block design with three replications, assessing 10 agronomic and tuber yield traits. The results showed significant variations among genotypes for all traits, which indicates the presence of genetic potential that can be harnessed for crop enhancement. The MGIDI index provided an increased total genetic gain of 78.58% for the desired traits. Specific genotypes, including PUT‐b (FA1), ADU‐b (FA2), OBR‐B, ENK‐B, ASU‐b (FA3), and BEP‐B (FA4), were identified as the top candidates for simultaneous improvement of the measured traits in tiger nut. This demonstrates the efficiency of the index in selecting superior genotypes, offering a data‐driven approach to breeding programs aimed at optimizing tiger nut yield and quality. Furthermore, the identification of specific high‐performing genotypes provides valuable genetic resources for future research and commercial cultivation. These findings contribute to the broader goal of improving food security and diversifying agricultural production. By promoting the genetic enhancement of tiger nut, this study supports its potential as a sustainable crop with significant nutritional and economic benefits.